Empowering youth through volunteerism: the importance of global motivating factors - Gombe, Sani Yakubu; Suandi, Turiman; Ismail, Ismi Arif; Omar, Zoharah (International Organization of Scientific Research, 2015)
Youth participation in volunteerism is a hidden approach that empowers them socially and psychologically, the positive effect in Nigeria is very high, because it promotes mutual cohesion among members of different background, level of education, ethnicity, culture, needs, aspiration and values. It also creates conscious future generation that will take the country to a greater height. However, studies regarding youth volunteerism in Nigeria are very scarce and the population of youth is increasing at alarming rate with a projected population of 2015 of about 56 million out which accounts for about 40% of the total population. Realizing the importance of volunteerism among youth in Nigeria, this paper presents an overview of motivating factors towards volunteerism across the globe and identifies specific factors that motivate youth to participate actively in volunteerism activities locally. The paper also identifies promoting mutual cohesion, enhancing capacity, motivating others to join, promoting philanthropy among the importance of volunteerism to the individual and the community at large. Altruism, level of education, collaboration, need to be with friends, self-motivation, age, gender, health status and intelligence are the major motivating factors of youth volunteerism in Nigeria.